Wear resistance and abrasiveness of CAD-CAM monolithic materials - Ludovichetti, Francesco Saverio [UNESP]; Trindade, Flávia Zardo [UNESP]; Werner, Arie; Kleverlaan, Cornelis Johannes; Fonseca, Renata Garcia [UNESP] (Elsevier, 2018)
Statement of problem: Computer-aided design and computer-aided manufacturing (CAD-CAM) restorations are in contact with the antagonist tooth, either a natural tooth or a restoration. Therefore, clinicians should be aware of the wear resistance of CAD-CAM materials and the wear behavior of the antagonist. Purpose: The purpose of this in vitro study was to evaluate the wear resistance and abrasiveness of CAD-CAM materials. Material and methods: In a 2-body wear test, the materials IPS e.max CAD (Ivoclar Vivadent AG), Vita Suprinity (Vita Zahnfabrik), Lava Ultimate (3M ESPE), Vita Enamic (Vita Zahnfabrik), and Lava Plus (3M ESPE) acted as abraders and, together with bovine enamel, also as antagonists. Each antagonist wheel ran against each abrader wheel for 200 000 cycles, with a spring force of 15 N, and at a rotational speed of 1 Hz in distilled water. The wear rate was determined with a surface profilometer. The surfaces were observed with scanning electron microscopy, and their hardness, coefficient of friction, and roughness were evaluated. Results: Lava Plus and IPS e.max CAD exhibited the highest potential for wear of Lava Ultimate. These 2 materials, together with Vita Suprinity, provided the highest wear of enamel and Vita Enamic. Vita Suprinity and IPS e.max CAD had higher wear than Lava Plus, and the inverse was also true. Vita Enamic and Lava Ultimate were among the materials that caused the lowest wear of enamel and all other evaluated materials. Scanning electron microscopy images revealed that except for Lava Ultimate, all other materials damaged enamel, in which Vita Suprinity and IPS e.max CAD were more aggressive when sliding against the materials. Lava Plus had the greatest hardness, followed by Vita Suprinity and IPS e.max CAD, Vita Enamic, and then Lava Ultimate. The coefficient of friction varied from 0.42 to 0.53. The Vita Enamic and Lava Ultimate showed the highest surface roughness. Conclusions: The nanofilled composite resin and polymer-infiltrated ceramic were more antagonist-friendly (whether enamel or CAD-CAM material) than glass-ceramics and zirconia. Care should be taken when selecting the material that will contact mainly with glass-ceramics. Hardness should also be considered when selecting a material.